2019
DOI: 10.1038/s41598-019-55055-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hypothermal stress-induced hepatic mitochondrial metabolic patterns between fresh water- and seawater-acclimated milkfish, Chanos chanos

Abstract: Milkfish (Chanos chanos) is a tropical euryhaline species. It can acclimate to fresh water (FW) or seawater (SW) and be cultured in both. In winter, cold snaps cause huge losses in milkfish revenue. Compared to FW-acclimated individuals, SW-acclimated milkfish have better low-temperature tolerance. Under hypothermal stress, a stable energy supply is critical to maintain normal liver function. In this study, the levels of key mitochondrial enzymes (citrate synthase (CS) and cytochrome c oxidase (COX)) in milkfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In winter, high mortalities have been recorded during cold snaps, which have caused enormous economic losses in Taiwan (Liao, 2016). Previous studies have shown that SW-acclimated milkfish exhibit a better cold tolerance than FW-acclimated fish (Kang et al, 2015), notably through differential energy utilization pathways (Chang et al, 2019(Chang et al, , 2020.…”
Section: Introductionmentioning
confidence: 98%
“…In winter, high mortalities have been recorded during cold snaps, which have caused enormous economic losses in Taiwan (Liao, 2016). Previous studies have shown that SW-acclimated milkfish exhibit a better cold tolerance than FW-acclimated fish (Kang et al, 2015), notably through differential energy utilization pathways (Chang et al, 2019(Chang et al, , 2020.…”
Section: Introductionmentioning
confidence: 98%
“…Among them, citrate synthase (CS), isocitrate dehydrogenase (IDH), and oxoglutarate dehydrogenase complex (OGDC) are the key enzymes in the TCA cycle. Previous studies found that the activity of CS, a key enzyme catalyzing the first step of the TCA cycle, was significantly increased and ATP was downregulated ( p < 0.05) in the livers of flounders under hypothermic stress . In contrast, the enzyme (p00889; 0.706-fold) expression level was significantly decreased in SNY livers ( p < 0.05).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies found that the activity of CS, a key enzyme catalyzing the first step of the TCA cycle, was significantly increased and ATP was downregulated (p < 0.05) in the livers of flounders under hypothermic stress. 20 In contrast, the enzyme (p00889; 0.706fold) expression level was significantly decreased in SNY livers (p < 0.05). As we did not explore the specific energy production, we can only speculate that plateau cold stress may induce a low activity state in CS.…”
Section: Tricarboxylic Acid (Tca) Cyclementioning
confidence: 90%
“…It suggested that the synergistic effects of LGP2 and MDA5 may be inconsistent in individuals with different levels of AST, resulting in an antiviral response that is the opposite. The activity of AST is known to be involved in the biosynthesis of mitochondrial amino acids ( Kirsch et al, 1984 ; Chang, Liu & Lee, 2019 ). Animal experiments show that the liver injury group showed higher mitochondrial oxygen consumption, higher enzyme activity, and higher ATP levels.…”
Section: Discussionmentioning
confidence: 99%